Association of plasma FGF21 levels with muscle mass and muscle strength in a national multicentre cohort study: Korean Frailty and Aging Cohort Study. (27th September 2021) - Roh, Eun; Hwang, Soon Young; Yoo, Hye Jin; Baik, Sei Hyun; Cho, Belong; Park, Yong Soon; Kim, Hyeon Ju; Lee, Sam-Gyu; Kim, Bong Jo; Jang, Hak Chul; Kim, Miji; Won, Chang Won; et al.
Abstract: Background: despite of the beneficial effects of fibroblast growth factor (FGF) 21 in several metabolic diseases, the association of plasma FGF21 with muscle mass and muscle strength is still unclear. Methods: a total of 386 community-dwelling older adults aged 70–84 years were analysed. Appendicular skeletal muscle mass was measured using dual-energy X-ray absorptiometry and normalised to the square of height (ASM/ht 2 ). Muscle strength was assessed using the hand grip strength (HGS) test. The definitions of low muscle mass (LMM) and low muscle strength (LMS) were based on the Asian Working Group for Sarcopenia. Results: plasma FGF21 was significantly lower in participants with LMM than in those with normal muscle mass (289.7 [192.4–448.3] vs. 345.6 [238.6–503.2] pg/ml, P  = 0.008). In contrast, the LMS group had a significantly higher plasma FGF21 level than the normal muscle strength group (369.7 [244.4–591.1] vs. 309.7 [205.3–444.8] pg/ml, P  = 0.006). In the partial correlation analysis, following adjustment for age, sex and body mass index, FGF21 levels had no significant association with ASM/ht 2, but were negatively associated with HGS ( r  = −0.112, P  = 0.029). Furthermore, after multivariate adjustment for confounding variables, the odds ratio for the risk of LMS was 2.32 (95% confidence interval 1.20–4.46) when comparing the highest with the lowest FGF21 quartile. Conclusions: circulating FGF21 levels are negatively associated with muscle strength but are not independently correlated with muscle mass.